Quantitative morphological analysis and digital modeling of polydisperse anisotropic carbon foam - Arand, Frederick; Hesser, Jürgen (Carbon, 2018)
Digital models of open cell carbon foam often approximate pore space by a set of overlapping spheres. In this paper, we extend this strategy to overlapping ellipsoids of varying size and anisotropy. A typical application is demonstrated: After a carbon foam sample is digitized with a computed tomography (CT) scanner, pores are analyzed with respect to polydispersity and anisotropy. Digital foam is created in two steps. First, a heuristic bubble growth simulation yields an overlapping ellipsoid packing, representing large pores. Small pores are then added to the remaining material. Finally, sample and digital model are compared by Finite Element (FE) analysis. Our results show that the foam model agrees well with the analyzed sample when considering pore statistics. However, mechanical simulations show differences, with an average effective elastic modulus of 0.341GPa for the sample, compared to 0.153GPa for the model. The approach of digital foam allows to assess the potential and limitation of diverse analysis techniques for CT scans of foam and hence gives respective limits. FE simulations help to identify accurateness of digital models.